2017
DOI: 10.23986/afsci.61076
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing an outperforming pea cultivar for intercropping with oat at high latitudes

Abstract: The cereal often dominates the grain legume in intercrops, especially when sown in larger amounts. This study assessed yield formation of pea (Pisum sativum L.) and oat (Avena sativa L.) in an intercropping system in high-latitude conditions. Three pea cultivars (Hulda, Karita and Perttu) and one oat cultivar (Roope) were grown as sole crops and intercrops with shares of either 7.5% or 15% of oat (as weight of sown seed mixture). Experiments were organized in three (southern, western and northern) locations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…The present study demonstrates, in a controlled greenhouse environment, that benefits of varietal diversity are apparent in intercrop situations with and without water limitation, although the observed effects of intraspecific diversity on intercrop performance were somewhat inconsistent. We found that the faba bean variety influences several important measures of intercrop performance, supporting the results of studies conducted on oat-pea intercrops (Peltonen-Sainio et al, 2017), maize-common bean intercrops (Isaacs et al, 2016), and maize-cowpea intercrop (Abera et al, 2017). In the present study, variations in above-and below-ground parameters related to plant growth, nodulation, and nutrient acquisition demonstrated that faba bean-wheat intercrops buffered biomass dry matter accumulation, nodulation, and N accumulation in water-limited faba bean (in intercrops containing the varieties WAJ) and wheat (in intercrops containing the variety Gloria).…”
Section: Discussionsupporting
confidence: 87%
“…The present study demonstrates, in a controlled greenhouse environment, that benefits of varietal diversity are apparent in intercrop situations with and without water limitation, although the observed effects of intraspecific diversity on intercrop performance were somewhat inconsistent. We found that the faba bean variety influences several important measures of intercrop performance, supporting the results of studies conducted on oat-pea intercrops (Peltonen-Sainio et al, 2017), maize-common bean intercrops (Isaacs et al, 2016), and maize-cowpea intercrop (Abera et al, 2017). In the present study, variations in above-and below-ground parameters related to plant growth, nodulation, and nutrient acquisition demonstrated that faba bean-wheat intercrops buffered biomass dry matter accumulation, nodulation, and N accumulation in water-limited faba bean (in intercrops containing the varieties WAJ) and wheat (in intercrops containing the variety Gloria).…”
Section: Discussionsupporting
confidence: 87%